KARAKTERISTIK PENDERITA DIABETES MELLITUS TIPE 2 DENGAN KOMPLIKASI YANG DIRAWAT INAP DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2016 - fitri nurmaya sirait; Hiswani .; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
ABSTRACT DM disease with complications becomes a public health problem. Prevalence of DM with complication 1.8% and the proportion of DM patients with complications 2.3% in North Sumatra in 2013. This study was conducted to determine the characteristics of patients with type 2 diabetes with complications are hospitalized at St. Hospital Elisabeth Medan in 2016. Type of descriptive research with case series design. The population of this research is all data of patient with Type 2 DM with complication which is hospitalized in year 2016 as many as 287 data and sample equal to 167 data of patient of type 2 DM by using technique of Simple Random Sampling. Types of data collected secondary data were analyzed by Chi-Square test and t-test. The results showed that the proportion of patients with type 2 diabetes with the highest complication in the age group was 46-55 years (32,3%), female gender (59,9%), age category >45 years 93,4% Batak (89,8%), Protestant Christianity (67,1%), employment is unemployed / retired / housewife (50,3%) and residence in Medan (55,1%). Fatigue / nausea and vomiting (79%), hypertension (37,1%), chronic complications (88,6%), HbA1c (46%), abnormal HbA1c examination (94.9%), blood levels of 200-399 mg/dl (56,9%), home treatment (88%), OHO (38,9%), BPJS cost source (51,5%), average treatment duration (5 day). There were no statistically significant differences in age (p=0,363), sex based on complication category (p=0,085), type of treatment based on complication category (p= 0,217), complication category based on home situation (p=1,00) and there was a significant difference of treatment type based on HbA1c (p=0,017). Expected to the St. Hospital. Elisabet Medan to check HbA1c levels in all patients with type 2 diabetes. It is recommended for all patients with type 2 diabetes with complications to check HbA1c levels. Patients with type 2 diabetes mellitus have uncontrolled HbA1c levels in order to improve lifestyle such as healthy food consumption, more exercise routine, consume medicine as directed by doctor, check HbA1c regularly every three months to check the success of treatment and prioritize insulin treatment to prevent complication which is more severe and check blood glucose levels regularly. Keywords: Characteristics, Type 2 DM, Complications